PERAN ORANGTUA DALAM MEMBENTUK ORIENTASI SEKSUAL PADA ANAK - Icha Marina Elliza (IAIN Padangsidimpuan, 2020)
Parents are the first people who will be role models for their children. Parents will be authoritative if there is a match between words and deeds. One of the roles of parents is to educate children according to their nature. This will affect their sexual orientation in the future. Both of parents, father and mother have an equal role in forming sexual orientation in children so that balance occurs and children are not biased about gender.